PM Pittsburgh Project (Tufts Archival Research Center, 2007)
Report regarding Philip Morris' Pittsburgh project. Discusses the strategy of Philip Morris in obtaining union support for their new program. Mentions the concerns the unions have which include the lack of a clean indoor air program and collective bargaining.